Sexual practices and HIV risk perception among men who have sex with men in Brazil - Araújo, Telma Maria Evangelista de (2024)
Funding Information: The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: Coordination for the Improvement of Higher Education Personnel (CAPES), Grant/Award Number: 001-2023. Publisher Copyright: © The Author(s) 2024.